Follow‐ups of the Cardiovascular Risk in Young Finns Study in 2001 and 2007: Levels and 6‐year changes in risk factors - Raiko, J. R. H.; Viikari, J. S. A.; Ilmanen, A.; Hutri‐Kähönen, N.; Taittonen, L.; Jokinen, E.; Pietikäinen, M.; Jula, A.; Loo, B.‐M.; Marniemi, J.; Lehtimäki, T.; Kähönen, M.; et al. (Journal of internal medicine, 2010)
.  Raiko JRH, Viikari JSA, Ilmanen A, Hutri‐Kähönen N, Taittonen L, Jokinen E, Pietikäinen M, Jula A, Loo B.‐M, Marniemi J, Lehtimäki T, Kähönen M, Rönnemaa T, Raitakari OT, Juonala M (University of Turku; University of Tampere and Tampere University Hospital, Tampere; University of Oulu, Oulu; Vaasa Central Hospital, Vaasa; University of Helsinki, Helsinki; and Center of Social and Health Services, Kuopio; Finland). Follow‐ups of the Cardiovascular Risk in Young Finns Study in 2001 and 2007: Levels and 6‐year changes in risk factors. J Intern Med 2010; 267: 370–384. Objectives.  To examine cardiovascular risk factor levels in 2007 and their 6‐year changes between 2001 and 2007 using the data collected in the follow‐ups of the Cardiovascular Risk in Young Finns Study. Design.  Population‐based follow‐up study. Subjects.  A total of 2204 healthy Finnish adults aged 30–45 years (1210 women; 994 men). Main outcome measures.  Levels in 2007 and changes between 2001 and 2007 of lipids, insulin, glucose, blood pressure, smoking, body mass index, alcohol consumption, waist and hip circumferences. Results.  The mean serum total cholesterol, low density lipoprotein (LDL) cholesterol, high density lipoprotein (HDL) cholesterol and triglyceride concentrations in 30‐ to 45‐year‐old adults were 5.05, 3.09, 1.34 and 1.40 mmol L−1, respectively. Significant changes (P < 0.05) between 2001 and 2007 in 30‐ to 39‐year‐old subjects included a decrease in total cholesterol (−6.6% in men, −5.8% in women), LDL‐cholesterol (−10.2% and −11.6%) and an increase in diastolic blood pressure (3.5% and 3.9%). Waist circumference (1.8% and 5.5%) and systolic blood pressure increased in 36–39 year olds (2.3% and 2.3%). HDL‐cholesterol increased in 30‐ to 33‐year‐old women (5.8%) Glucose levels increased in 30‐ to 39‐year‐old women (3.7%) and 36‐ to 39‐year‐old men (3.6%). Smoking prevalence decreased in 36‐ to 39‐year‐old men from 29.8% to 22.2%. Conclusions.  The 6‐year changes in total cholesterol, LDL‐cholesterol and HDL‐cholesterol in young Finns were favourable between 2001 and 2007. However, waist circumference, glucose and blood pressure levels increased. Therefore, continuous efforts are still needed in fighting against cardiovascular risk factors.